(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To identify factors predicting pregnancy outcomes in patients undergoing day-5 frozen embryo transfer cultured with the Timelapse system at Hanoi Obstetrics and Gynecology Hospital. Method: A cross-sectional descriptive study conducted on 221 infertile patients who underwent day-5 frozen embryo transfer at Hanoi Obstetrics and Gynecology Hospital from June 2023 to May 2024. Results: The KIDs score, ICM quality, and TE quality were significantly related to the pregnancy outcome. The highest pregnancy rates were observed in embryos with ICM and TE of grade A, with rates of 62.1% and 47.7%, respectively (p < 0.05). Multivariable logistic regression analysis identified 3 independent predictors of pregnancy outcomes: maternal age (≤ 35 years old had a pregnancy rate 3.482 times higher than > 35 years), history of miscarriage/stillbirth (no history had a pregnancy rate 2.066 times higher), and KIDs score (greater than 7.15 had a pregnancy rate 3.509 times higher). Conclusions: Embryos with good ICM and TE quality cultured with the Timelapse system enhance pregnancy rates. The predictors of pregnancy outcomes include maternal age, history of miscarriage/stillbirth, and KIDs score.